2003
DOI: 10.1097/01.brs.0000084877.88192.8e
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Interspinous Implant on the Kinematics of the Instrumented and Adjacent Levels in the Lumbar Spine

Abstract: The implant does not significantly alter the kinematics of the motion segments adjacent to the instrumented level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
105
0
15

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(131 citation statements)
references
References 27 publications
9
105
0
15
Order By: Relevance
“…We could show that the pressure decreased in extension with all implants. This is also in agreement with a study by Swanson et al [11] using the X-Stop, who measured the intradiscal pressure at the instrumented and the adjacent levels with the same study design as Lindsey et al [7]. They could show, that there was a strong decrease of the IDP in the instrumented segment during extension without significant effect at the adjacent levels.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We could show that the pressure decreased in extension with all implants. This is also in agreement with a study by Swanson et al [11] using the X-Stop, who measured the intradiscal pressure at the instrumented and the adjacent levels with the same study design as Lindsey et al [7]. They could show, that there was a strong decrease of the IDP in the instrumented segment during extension without significant effect at the adjacent levels.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, it could be shown that this load is almost physiological if the anterior column of the spine is intact [7]. During loading the specimens were allowed to move unconstrained in the five uncontrolled degrees of freedom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the previous relative studies have correlated ''static'' radiographic criteria (DH, traction spurs, osteophytes, etc) with clinical symptoms [3,37,45]. Others have additionally used advanced imaging techniques as computed tomography (CT), magnetic resonance imaging (MRI) [13,25,53,63].…”
Section: Discussionmentioning
confidence: 99%